1987
DOI: 10.1111/j.1751-1097.1987.tb05363.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Cutaneous Photosensitizing Agents—ix. A Spin Trapping Study of the Photolysis of Amiodarone and Desethylamiodarone

Abstract: The photolysis of amiodarone (AM) and its major metabolite mono‐N‐desethylamiodarone (DEA), has been studied by absorption spectroscopy, electron spin resonance spectroscopy (spin trapping) and oxygraph measurements. Changes in the absorption spectrum of both AM and DEA upon UV irradiation indicate that both drugs undergo deiodination. Spin trapping experiments with 2‐methyl‐2‐nitrosopropane (MNP), α‐phenyl‐N‐tert‐butyl‐nitrone (PBN) and 5.5‐dimethyl‐1‐pyrroline‐N‐oxide (DMPO) suggest the formation of an aryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 30 publications
(20 reference statements)
4
16
0
Order By: Relevance
“…3E). The hyperfine splitting parameters of these adducts (Table 1) were similar to previously reported values (Li and Chignell, 1987b). When FT was replaced by BT, identical results were obtained (data not shown).…”
Section: Anaerobic Photolysissupporting
confidence: 89%
See 1 more Smart Citation
“…3E). The hyperfine splitting parameters of these adducts (Table 1) were similar to previously reported values (Li and Chignell, 1987b). When FT was replaced by BT, identical results were obtained (data not shown).…”
Section: Anaerobic Photolysissupporting
confidence: 89%
“…Haloaromatic compounds are known to generate aryl radicals and free halogen atoms upon UV photolysis (Grimshaw and de Silva, 1981). Recent reports include amiodarone (Li and Chignell, 1987b), chlorpromazine (Motten et al, 1985) and 2-(4-halophenyl)benzoxazoles (Fery-Forgues and Paillous, 1986). The formation of aryl radicals during the photodehalogenation of polyhalogenated phenols has long been postulated or implicated (Horio, 1984;Johnson, 1984;O'Quinn et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Amiodarone in vitro and in vivo has been shown to generate free radicals that may be involved in the pathogenesis of its toxicity [1][2][3][4][5][6][7][8] and in its reduction in cellular immunity. 9 The potential mechanisms of amiodarone-induced toxicity include direct cytotoxicity, the development of lysosomal phospholipidosis, indirect immunologically mediated toxic effects, and membrane destabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that yeast cells were sensitized and killed by adriamycin after irradiation at 365nm, a wavelength that presented no effect in the absence of the drug. Also, cytotoxicity of several anthracycline derivatives are significantly enhanced by continuous wave green light of argon (514nm) or KTP (532nm) laser illumination of different types of cancer, both in vitro (Li and Chignell, 1987;Paiva et al, 1996) and in vivo. (Nahabedian et al, 1988;Peavy et al, 1992;Soudant et al, 1992;Paiva et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Both drugs cause oxidative damage to cardiac tissue even in the absence of light. However, spin label experiments have been reported that show light activation of these drugs induces chemical bonding to many different cell membrane proteins (Li and Chignell, 1987). Anthracyclines initially bind to tumor cell membranes before transport in the nucleus and are considered to be poor type-II photosensitizers, which do not generate significant amounts of singlet oxygen (Andreoni et al, 1993).…”
Section: Introductionmentioning
confidence: 99%